Selected methods of the Reading and Writing for Critical Thinking programme in teaching individuals with a different mother tongue - Tušková, Marie Jana; Svobodová, Hana (Bohemica Olomucensia, 2023)
The paper focuses on the possibilities of using selected methods and procedures of the Reading and Writing for Critical Thinking programme in teaching individuals with a different mother tongue. Most of them develop reading literacy understood as the ability to understand, reflect on and use written text to achieve certain goals, i.e. to develop one's own skills and knowledge and to actively participate in society. The essence of the paper consists of examples of practical use of selected methods of critical thinking in tea- ching Czech as a second/foreign language, which serve to motivate and develop writing and speaking.
Keywords: Critikal thinking; procedures and methods; reading literacy; teaching Czech as a second/foreign language